And Then There Were Three: Effects of Pretransplant Dialysis on Multiorgan Transplantation. Issue 2 (February 2021) - Cheng, Xingxing S.; Han, Jialin; Stedman, Margaret R.; Chertow, Glenn M.; Tan, Jane C.
Abstract : Background: Simultaneous liver-kidney (SLK) and simultaneous heart-kidney (SHK) transplantation currently utilize 6% of deceased donor kidneys in the United States. To what extent residual kidney function accounts for apparent kidney allograft survival is unknown. Methods: We examined all adult SLK and SHK transplants in the United States during 1995–2014. We considered the duration of dialysis preceding SLK or SHK (≥90 d, 1–89 d, or none) as a proxy of residual kidney function. We used multinomial logistic regression to estimate the difference in the adjusted likelihood of 6- and 12-month apparent kidney allograft failure between the no dialysis versus ≥90 days dialysis groups. Results: Of 4875 SLK and 848 SHK recipients, 1775 (36%) SLK and 449 (53%) SHK recipients received no dialysis before transplant. The likelihood of apparent kidney allograft failure was 1%–3% lower at 12 months in SLK and SHK recipients who did not require pretransplant dialysis relative to recipients who required ≥90 days of pretransplant dialysis. Among 3978 SLK recipients who survived to 1 year, no pretransplant dialysis was associated with a lower risk of apparent kidney allograft failure over a median follow-up of 5.7 years (adjusted hazard ratio 0.73 [0.55–0.96]). Conclusions: Patients with residual kidney function at the time of multiorgan transplantation are less likely to have apparent failure of the kidney allograft. Whether residual kidney function facilitates function of the allograft or whether some SLK and SHK recipients have 3 functional kidneys is unknown. Sustained kidney function after SLK and SHK transplants does not necessarily indicate successful MOT.